Arctic fishes reveal patterns in radiocarbon age across habitats and with recent climate change - Ashley E. Stanek; Jonathan A. O'Donnell; Michael P. Carey; Sarah M. Laske; Xiaomei Xu; Kenneth H. Dunton; Vanessa R. von Biela (Limnology and Oceanography Letters)
Abstract Climate change alters the sources and age of carbon in Arctic food webs by fostering the release of older carbon from degrading permafrost. Radiocarbon (14C) traces carbon sources and age, but data before rapid warming are rare and limit assessments over time. We capitalized on 14C data collected ~ 40 years ago that used fish as natural samplers by resampling the same species today. Among resampled fish, those using freshwater food webs had the oldest 14C ages (> 1000 yr BP), while those using marine food webs had the youngest 14C ages (near modern). One migratory species encompassed the entire range of 14C ages because juveniles fed in freshwater streams and adults fed in offshore marine habitats. Over ~ 40 yr, average 14C ages of freshwater and marine feeding fish shifted closer to atmospheric values, suggesting a potential influence from “greening of the Arctic.”